(untitled) (Tanzania Journal for Population studies and Development, 2019)
This paper intends to examine the private returns to education in Tanzania using three different Integrated Labour Force Survey data collected in 2001, 2006 and 2014. The estimation of the rate of returns to education was presented separately by each year data. The estimation was also carried out by comparing between males and females sub-samples. Using Ordinary Least Squares (OLS) technique, we find private returns to education increases with the levels of education over the 2001-2014 periods. We observed further the patterns tend to decrease over time, despite rising average levels of schooling attainment. Additionally, females experience a higher rate of return than males. These findings have important policy implications with respect to strengthening the public funding of tertiary education suggesting that increasing public expenditure on tertiary education is necessary for greater equality and poverty alleviation in Tanzania.